2023
DOI: 10.3892/mi.2023.83
|View full text |Cite
|
Sign up to set email alerts
|

New‑onset non‑motor symptoms in patients with Parkinson's disease and post‑COVID‑19 syndrome: A prospective cross‑sectional study

Abstract: the clinical range of post-coronavirus disease 2019 symptoms in patients with Parkinson's disease (PD) has not yet been thoroughly characterized, with the exception of a few small case studies. the aim of the present study was to investigate the motor and non-motor progression of patients with PD (PWP) and post-CoVID-19 syndrome (PCS) at baseline and at 6 months after infection with CoVID-19. a cross-sectional prospective study of 38 PWP+/PCS+ and 20 PWP+/PCS-matched for age, sex and disease duration was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…None thus far have directly compared the long-term outcomes of PD patients, with and without a history of SARS-CoV-2 infection. Bougea et al [42] studied PD patients with COVID-19 at baseline and at six months postinfection using clinicodemographic questionnaire. They found that among those with who reported post-COVID-19 syndrome, levodopa equivalent daily dose and Uni ed Parkinson's Disease Rating Scale Part III increased after infection, indicating possibly elevated disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…None thus far have directly compared the long-term outcomes of PD patients, with and without a history of SARS-CoV-2 infection. Bougea et al [42] studied PD patients with COVID-19 at baseline and at six months postinfection using clinicodemographic questionnaire. They found that among those with who reported post-COVID-19 syndrome, levodopa equivalent daily dose and Uni ed Parkinson's Disease Rating Scale Part III increased after infection, indicating possibly elevated disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…By developing an understanding of these parallels, it may be possible to increase resilience to both pandemics. Strategies for managing post-pandemic health should consider the long-term health consequences of COVID-19 and obesity, since lingering issues and chronic conditions may continue to exist after a pandemic has passed ( 12 , 13 , 25-27 ).…”
Section: The Interconnectedness Of Covid-19 and Obesitymentioning
confidence: 99%
“…Hepatic damage, as evidenced by increased levels of circulating liver enzymes, is also prevalent ( 3 ). There are several symptoms that may be associated with peripheral and central nervous system involvement, and these include headaches and dizziness, hyposmia or anosmia (indicative of encephalopathy), neuralgia and Guillain-Barré syndrome ( 115 , 116 ). Hospitalized patients are more likely to experience thromboembolic events, which have been established as an independent risk factor for a poor prognosis, and acute coronary modalities, cardiomyopathies, several types of arrhythmias, pericarditis and various thromboembolic events ( 49 , 117 ).…”
Section: Pathophysiology and Long-term Repercussions Of Covid-19mentioning
confidence: 99%